Erosion of Co-Cr-W alloy and coating on its basis under the action of cavitation - Kovalenko, V.I.; Klimenko, A.A.; Martynenko, L.I.; Marinin, V.G. (Вопросы атомной науки и техники, 2019)
The average destruction rates (Vs) were measured under the action of cavitation on a pre-production model from the alloy of Co-Cr-W on chemical composition near to the stellite No.6, its initial components and the coating obtained from a powder of the same composition using plasma generated by a plasma torch. It is established that the average destruction rate (Vs) of chromium, cobalt, tungsten is equal to 3.5; 0.72; 0.56 µm/h, respectively, and Co-Cr-W – 0.5 µm/h. After heat treatment of the Co-Cr-W alloy at a temperature of 1300 K for 3.6 ks, the value of Vs decreases to 0.28 µm/h. The plasma coating is destroyed at a speed of 1.3 µm/h, and steel 15Kh11MF – 2.4 µm/h. Under the action of cavitation in a corrosive environment, a 3% aqueous solution of sodium chloride Vs steel 15Kh11MF and Co-Cr-W alloy increases by 2 times.